PENGEMBANGAN PERANGKAT PEMBELAJARAN BIOLOGI BERBASIS KURIKULUM 2013 PADA MATERI SISTEM EKSKRESI KELAS XI SMA - Yusti, Isra Layla Yusti Layla; Suryawati, Evi Suryawati; Sayuti, Irda Sayuti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract : This research aims to development of biology learning device based curriculum 2013 in the excretion system topic class XI senior high school. Biology learning device delevoped include syllabus, lesson plan, student worksheet, authentic assessment, and learning media. Development process conducted at the Campus Biology Education FKIP Riau University and limited trial at SMAN Plus Riau Province on March â€“ June 2015. This research used Research and Development approach with ADDIE models which is conducted to implementation by limited trial. Subject this research consist of Basic Competence 3.9 contained in class XI SMA. The data collection instruments used were the validation sheet. This validation sheet filled by internal validator and external validator. The collected data were statistically analyzed descriptive. The results of validity learning device are valid for lesson plan, worksheets, written assessment, and learning media and very valid for attitude assessment, performance assessment, product assessment, project assessment, self-assessment and portfolio assessment. The results of limited trial to the LKS, written tests, and self-assessment are tested on XI.MS.1 class SMAN Plus Riau province with the number of students as many as 21 people were good and excellent. From the results of the validation study it can be concluded that the device developed Biology potentially can be implemented through field trials. Key words: biology senior high school, development, learning device, curriculum 2013 Â